Growth of bainitic ferrite and carbon partitioning during the early stages of bainite transformation in a 2 mass% silicon steel studied by in situ neutron diffraction, TEM and APT. Issue 2 (16th February 2016) - Timokhina, I. B.; Liss, K. D.; Raabe, D.; Rakha, K.; Beladi, H.; Xiong, X. Y.; Hodgson, P. D.
Abstract : The current work investigates key aspects of the evolution of nano‐bainite formation at low isothermal temperature during the early stages of the transformation in a high Si steel using neutron diffraction, transmission electron microscopy (TEM) and atom probe tomography (APT) techniques. Abstract : In situ neutron diffraction, transmission electron microscopy (TEM) and atom probe tomography (APT) have been used to study the early stages of bainite transformation in a 2 mass% Si nano‐bainitic steel. It was observed that carbon redistribution between the bainitic ferrite and retained austenite at the early stages of the bainite transformation at low isothermal holding occurred in the following sequence: (i) formation of bainitic ferrite nuclei within carbon‐depleted regions immediately after the beginning of isothermal treatment; (ii) carbon partitioning immediately after the formation of bainitic ferrite nuclei but substantial carbon diffusion only after 33 min of bainite isothermal holding; (iii) formation of the carbon‐enriched remaining austenite in the vicinity of bainitic laths at the beginning of the transformation; (iv) segregation of carbon to the dislocations near the austenite/ferrite interface; and (v) homogeneous redistribution of carbon within the remaining austenite with the progress of the transformation and with the formation of bainitic ferrite colonies. Bainitic ferrite nucleated at internal defects or bainite/austenite interfaces as well as at the prior austenite grain boundary. Bainitic ferrite has been observed in the form of an individual layer, a colony of layers and a layer with sideplates at the early stages of transformation.